Reasonable stopping method and retracement channel support at fully mechanized top coal caving working face of 15 m extra‐thick coal seam: A case study - Shengrong Xie; Yiyi Wu; Xiang Ma; Dongdong Chen; Fangfang Guo; Zaisheng Jiang; Hui Li; Hang Zou; Ruipeng Liu; Xiao Zhang (Energy Science & Engineering, 2022)
Abstract Extra‐thick coal seams are widely distributed in the Datong mine area in China. The rapid stopping of mining and the support withdrawal technology for extra‐thick coal seams need to be developed urgently. The reasonable stopping top coal caving distance, main roof's fracture line position, and large section roadway during the stopping period (LSRSP) support method of the header face of 15 m extra‐thick coal seam are systematically studied by using field measurement, experiment, numerical simulation, and similar material simulation methods. With the increase in stopping coal caving distance, the range of the medium and low displacement zone of the LSRSP overburden gradually expands. In contrast, the depth of the plastic zone decreases. The scope and intensity of the high‐stress area of the overlying rock in front gradually decrease and shift from deep to the outside, while the peak stress area shifts from the top coal area to the coal rib of the retracement channel. Comparing the stopping of medium‐thick and thick coal seam working face, the interaction between “main roof−unmined top coal−supports” is analyzed. The unique characteristics of the extra‐thick coal seam working face are derived: when the stopping coal caving distance is shorter than the length of the key block, the dropped coal body cannot effectively restrict the movement of key blocks. Mutual compression and subsidence occur between key blocks, making the broken coal rock block squeeze into the supports. By the simulation study of each index, the stopping coal caving distance of the extra‐thick coal seam is optimal when it is slightly larger than the length of the key block (i.e., the periodic weighting step), simultaneously, the main roof fracture line behind the supports is most favorable for stopping mining. After ensuring the stability of the LSRSP's overburden structure, the differentiated support scheme of “controlled zoning−strength grading” was proposed, and the scheme was modified and verified by simulating the support prestress field. After field practice, the roof of the retracement channel is better controlled in deformation under the joint horizontal and vertical support, the robust control effect of the combined anchor cable is noticeable, the integrity of the polyurethane network is more substantial, and the working face supports have successfully achieved a safe and rapid evacuation.